2023
DOI: 10.1002/btpr.3346
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic features reveal molecular signatures associated with recombinant adeno‐associated virus production in HEK293 cells

Abstract: The development of gene therapies based on recombinant adeno‐associated viruses (rAAVs) has grown exponentially, so the current rAAV manufacturing platform needs to be more efficient to satisfy rising demands. Viral production exerts great demand on cellular substrates, energy, and machinery; therefore, viral production relies heavily on the physiology of the host cell. Transcriptomics, as a mechanism‐driven tool, was applied to identify significantly regulated pathways and to study cellular features of the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Recent transcriptional studies have implicated many of the same pathways and processes we identified in AAV production, despite variations in study design including plasmid and cell sources, transfection conditions, and growth media (Supplementary file 3). Wang et al (2023) identified several upregulated stress response and homeostatic proteins which align with our data, including HBB, HSPA6, and CCL5, as well as microtubule-interacting proteins including STMN4 and DNAH17 (Figure 3 -figure supplement 1A-C).…”
Section: Rna-seq Analysis Identifies Differentially Expressed Pathway...supporting
confidence: 83%
“…Recent transcriptional studies have implicated many of the same pathways and processes we identified in AAV production, despite variations in study design including plasmid and cell sources, transfection conditions, and growth media (Supplementary file 3). Wang et al (2023) identified several upregulated stress response and homeostatic proteins which align with our data, including HBB, HSPA6, and CCL5, as well as microtubule-interacting proteins including STMN4 and DNAH17 (Figure 3 -figure supplement 1A-C).…”
Section: Rna-seq Analysis Identifies Differentially Expressed Pathway...supporting
confidence: 83%
“…Given that viral proteins and viral nucleic acids are perceived as exogenous entities within the host cell milieu, their presence has the potential to trigger a series of host cell stress reactions, including but not limited to autophagy, endoplasmic reticulum (ER) stress, and programmed cell death (apoptosis). Our investigation unveiled an increased activation of these stress responses during phases associated with viral production 4,7,26,3741 (Fig. 5-7).…”
Section: Discussionmentioning
confidence: 52%
“…Further, the host cell's innate immune response typically serves as the initial barrier against viral dissemination. It has been documented that, within the conventional transfection parameters applied to the HEK293 cell line, the host cell's innate immune system tends to exhibit an upregulation 8,[26][27][28][29][30][31][32] . However, in our case, when comparing our optimal transfection conditions to the standard ones, we observed a notable downregulation or reduced expression of proteins associated with immune response (such as ASAH1, CREB1, CD81, POLR3F, STOM, ATP11B, ATP6V1C1, NFKB2) across the time points (Supplementary Data GO Analysis).…”
Section: Discussionmentioning
confidence: 99%
“…In a proteomic investigation of rAAV5 production by plasmid transfection of HEK293 cells, it was reported that the defense response was significantly enriched compared to untransfected cells (Strasser et al 2021 ). Another transcriptomic study of rAAV2 production by plasmid transfection of HEK293 cells reported significant upregulation of the signaling pathways of pattern recognition receptors (PRR), including Toll-like receptor (TLR), retinoic acid-inducible gene-I (RIG-I)-like receptor (RLR), nucleotide oligomerization domain (NOD)-like receptor, and cytosolic DNA-sensing pathways (Wang et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%